Pola Adaptasi Mahasiswa Baru Dalam Meraih Prestasi Akademik (Studi Kasus Adaptasi Mahasiswa China di UIN Maulana Malik Ibrahim Malang) - M. Ibnu Ahmad (Ta`Limuna: Jurnal Pendidikan Islam, 2021)
AbstractsThis study aims to understand the adaptation process of Chinese students in the first year with the culture of local students UIN Maliki Malang. The research method uses qualitative with a single case study design. The data of this study were collected from four Chinese students of UIN Malang in the academic year 2017/2018 through in- depth interview techniques. While data analysis is done using interactive analysis techniques. The findings of this study are: (1) the process of adaptation of Chinese students to the culture of local students goes through three important stages, namely: (a) adaptation to temperature, weather, and food taste; (b) the language of communication and local student accent; and (c) students' values, norms and local wisdom. In the process, Chinese students experience anxiety and uncertainty. To overcome this they learn to understand, accept and be open to the host culture. (2) The obstacles in the adaptation process are: (a) internal factors, namely inferiority complex; and (b) external factors, namely stereo type from local students and the language of communication. Keywords: Adaptation, Chinese students, host culture Â AbstrakKajian ini bertujuan untuk memahami proses adaptasi mahasiswa China pada tahun pertama dengan budaya mahasiswa lokal UIN Maliki Malang. Penelitian ini menggunakan metode penelitian kualitatif dengan rancangan studi kasus tunggal. Data penelitian dihimpun dari empat mahasiswa China UIN Malang tahun akademik 2017/2018 dengan melalui teknik wawancara mendalam. Sementara analisis data dilakukan memakai teknik analisis interaktif. Temuan penelitian ini adalah: (1) proses adaptasi mahasiswa China dengan budaya mahasiswa lokal dilalui dengan tiga tahapan penting yaitu: (a) adaptasi dengan suhu, cuaca, dan cita rasa makanan; (b) bahasa komunikasi dan dialeg mahasiswa lokal; dan (c) nilai, norma dan kearifan lokal mahasiswa. Dalam proses tersebut, mahasiswa China mengalami kecemasan dan ketidakpastian. Untuk mengatasinya mereka belajar memahami, menerima dan terbuka dengan host culture. (2) Hambatan dalam proses adaptasi tersebut adalah: rendah diri; stereo type dari mahasiswa lokal serta bahasa komunikasi yang tidak lancar. Kata Kunci: Adaptasi, Mahasiswa China, host culture